Time-varying factor premia in Nordic equities market - Laine, Juho (2021)
Factor premia is a reward for taking on all of the risk in Nordic capital markets. Many important characteristics of factor investing have already been established, such as the significance of factor timing and existence of global factor premia in multiple asset classes. However, the reasons for time variation of factor excess returns, are poorly understood. Therefore, the aim of this thesis is to determine whether the performance of the selected factors is consistent across Nordic stock markets and time, as well as which variables may be explaining the time-varying performance differences in factor performance.